Ushuaia pluton: Magma diversification, emplacement and relation with regional tectonics in the southernmost Andes - Gonzalez Guillot, Mauricio Alberto (2018)
The Ushuaia pluton (UP) and the Ushuaia Peninsula Andesites (UPA) are intrusive units of a Late Cretaceous rear-arc in the Southernmost Andes. We report new LA-ICP-MS zircon ages from ∼71 to 75 Ma for the UP, and of ∼84 Ma for the UPA, which allow to differentiate these two magmatic events; consistent with their distinct petrography and geochemistry. The UP is a composite, incrementally assembled pluton in upper crustal levels. Successive injections of magma batches define two main sections, each in turn constructed by several smaller pulses: an early ultramafic-mafic section consists mainly of hornblende pyroxenite, hornblendite and gabbro/diorite with reverse concentric zonation, and a later intermediate section built up mainly by monzodiorite. Mingling and layering between mafic and intermediate facies along the contact point to simultaneous emplacement at the end of one main pulse and the beginning of the other. Mineralogy and geochemistry suggest the rock sequence in the UP is cogenetic. In part it resulted by in-situ magmatic processes that included crystal-melt fractionation during injection of magma mushes, mingling, local melt segregation and mixing with crustal partial melts. The country rock is affected by penetrative ductile deformation and regional metamorphism developed during mid-Cretaceous Andean main orogenic phase. It also shows an overimposed pluton-margin parallel foliation and a post-kinematic contact metamorphic aureole. On the other hand, the UP has a concentric igneous foliation parallel to pluton margins interpreted as a primary magmatic feature. The above evidences, along with absence of subsolidus fabrics and metamorphism, indicate the pluton post-date peak regional metamorphism and ductile structures in the country rock. The new zircon ages constrain the top age of early Andean deformation, as well as the magmatic gap registered for the end of the Cretaceous, and confirm an emplacement during a recorded compressive regime that transmitted shortening to the foreland.